What accounts for the emergence of Malthusian fertility in transition economies? - Maja B. Micevska; Paul J. Zak (Claremont McKenna College, Department of Economics, 2002)
The transition to market-oriented economies in Central and Eastern Europe and the former Soviet Union in the 1990s, like the Great Depression in the U.S. and Germany in the 1930s, generated sharp declines in real incomes and a corresponding drop in fertility. This is contrary to the robust negative relationship between income and fertility that has been extensively documented. This paper presents a theoretical model that explains the positive relationship between fertility and income. The model predicts that: i) the perceived level of subsistence consumption fundamentally determines whether fertility and income are positively or negatively related; ii) once incomes decline below a threshold, declining labor income causes fertility to fall; and iii) rising income inequality has a negative impact on fertility rates. Empirical tests using both aggregate and microeconomic data provide strong support for the predictions of the model. Our empirics predict that the perceived subsistence level is a statistically significant determinant of fertility and that the average country in our sample will remain in a Mathusian fertility regime for twenty more years.
Keywords: J13; P20; I31; 330; Fertility; Subsistence Consumption; Transition.; Bevölkerungstheorie; Fruchtbarkeit; Einkommen; Subsistenzwirtschaft; Osteuropa